Fingolimod Reduces Hemorrhagic Transformation Associated With Delayed tPA Treatment In A Mouse Thromboembolic Model - Campos, Francisco (2013)
BACKGROUND AND PURPOSE: The sphingosine 1-phosphate receptor agonist fingolimod reduces infarct size in rodent models of stroke and enhances Blood Brain Barrier (BBB) integrity. Based on these observations, we hypothesized that combination of fingolimod with tissue Plasminogen Activator (tPA) would reduce the risk of hemorrhagic transformation associated with delayed administration of tPA. METHODS: We evaluated the effects of fingolimod in a mouse model of thromboembolic stroke, in which both the beneficial effect of reperfusion associated with early tPA treatment and hemorrhagic transformation associated with delayed administration mimic clinical observations in humans. RESULTS: Our results demonstrate that fingolimod treatment attenuates the neurological deficit and reduces infarct volume after in situ thromboembolic occlusion of the middle cerebral artery. Combination of fingolimod and tPA improves the neurological outcome of the thrombolytic therapy and reduces the risk of hemorrhagic transformation associated to delayed administration to tPA. CONCLUSION: This study confirms the protective efficacy of fingolimod as a treatment against ischemic stroke in another rodent model of stroke (thromboembolic occlusion), and suggests that fingolimod could potentially be used in combination with tPA to reduce the risk of brain hemorrhage.